Damage caused by exposure to propofol during gestation of mice (Acta Scientiarum. Health Sciences, 2017)
Literature shows that surgical procedure could be necessary at any stage of pregnancy and can cause adverse effects on the mother and fetus. One of the most used anesthetics in surgical centers is propofol however; the safety during pregnancy has not been completely established. The objective of this study was to investigate the possible toxic and teratogenic effects on the intrauterine and post-natal development of mice exposed to the dose of 15 mg kg-1 propofol on the caudal vein fifth, tenth and fifteenth day of gestation. A significant reduction in weight gain was observed in female mice who received a 15 mg kg-1 dose of propofol on the fifth gestational day. A higher rate of embryonic loss post implantation and resorption was also observed in this group. In regards to physical development, the anesthetic increased significantly the offspring weight gain, the time in which pinna detachment occurred, and the anogenital distance of pups whose females received propofol on the fifteenth day of gestation. Based on these results, we concluded that administration of propofol in the beginning stages of gestation increases the number of abortions and promotes alterations in the physical development of pups whose mothers were anesthetized in the final stages of gestation.